Тепловое поле алмазной коронки при бурении с нестационарным режимом промывки скважины - Кожевников, А.А.; Гошовский, С.В.; Дреус, А.Ю.; Мартыненко, И.И. ("Доповіді НАН України", 2007)
The mathematical model and the results of a numerical study of the temperature regime of a diamond drilling tool under nonstationary heat exchange with a washing fluid are presented.